2020
DOI: 10.1177/0032258x20917442
|View full text |Cite
|
Sign up to set email alerts
|

The ‘cost’ of caring in policing: From burnout to PTSD in police officers in England and Wales

Abstract: This article looks at secondary trauma of police officers caused by working with traumatised victims, examining what is the true ‘cost of caring’ for police officers in England and Wales. It will discuss common work-related ‘stressors’ in policing and review the concepts commonly associated with secondary trauma such as ‘burnout’, ‘vicarious trauma’, ‘compassion fatigue’, ‘secondary traumatic stress’ and their impact. It will conclude with some recommendations and highlight the serious lack of literature on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 94 publications
(133 reference statements)
2
19
0
Order By: Relevance
“…Resilient coping correlated negatively with emotion-orientated and positively with task and avoidance coping, suggesting avoidance strategies are sometimes used for managing stress [ 44 , 69 ]. These results are in line with other studies and confirm that policing is a stressful professional occupation [ 1 , 2 , 15 , 28 ] and that burnout affects police officers [ 4 , 6 , 24 , 27 ]. Moreover, results confirmed the preference of task-orientated coping among police officers [ 41 , 43 , 44 , 45 ], despite low values of resilience coping.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Resilient coping correlated negatively with emotion-orientated and positively with task and avoidance coping, suggesting avoidance strategies are sometimes used for managing stress [ 44 , 69 ]. These results are in line with other studies and confirm that policing is a stressful professional occupation [ 1 , 2 , 15 , 28 ] and that burnout affects police officers [ 4 , 6 , 24 , 27 ]. Moreover, results confirmed the preference of task-orientated coping among police officers [ 41 , 43 , 44 , 45 ], despite low values of resilience coping.…”
Section: Discussionsupporting
confidence: 92%
“…When the response to chronic job stress is inadequate, burnout appears as an occupational phenomenon [ 20 , 21 ] defined as a “prolonged response to chronic emotional and interpersonal stressors on the job, [expressed on] three dimensions of exhaustion, cynicism and inefficacy” [ 22 ] (p. 397). Regarding police officers’ burnout, innumerous studies found high levels of exhaustion and depersonalization, relationships between burnout and mental/psychological problems such as anxiety, depression and post-traumatic stress disorder [ 4 , 23 , 24 , 25 , 26 ], as well as depersonalization as a coping strategy, emotional suppression and difficulties to express true emotions [ 27 ]. Furthermore, police officers’ burnout can be related with internal or external aggression, a current social and political concern.…”
Section: Introductionmentioning
confidence: 99%
“…The trauma related to mental-health disorders of post-traumatic stress disorder (PTSD), anxiety, depression and burnout are four of the most prevalent and debilitating mental-health conditions worldwide [ 5 ]. Among them, PTSD and burnout are the most commonly studied consequences of workplace violence [ 18 , 19 , 20 , 21 ], with fewer efforts focused on anxiety and depression [ 22 , 23 ]. Research with nurses has demonstrated similar results, with more intense exposure (operationalized as more frequent exposure to one or more types of workplace violence) having been linked to higher levels in mental-health outcomes including PTSD, burnout, anxiety, depression and insomnia among nurses [ 6 , 7 , 13 , 22 , 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…This might be the result of potential cognitive decline connected with aging, which gradually decreases the ability to process traumatic events (Foa and Kozak 1986). Length of service also seems to increase the odds of developing symptoms of post-traumatic stress disorder, which might be the result of high demands and low resources in the workplace and burnout (Acquadro Maran et al 2020;Foley and Massey 2020). In the case of number of types of traumatic events, the more diversified the traumatogenic stimuli, the higher are the odds of developing PTSD symptomatology (similar results were found by Hartley et al (2013).…”
Section: Discussionmentioning
confidence: 99%